2014
DOI: 10.1161/circulationaha.113.005544
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Trial of Ultrasound-Assisted Catheter-Directed Thrombolysis for Acute Intermediate-Risk Pulmonary Embolism

Abstract: A cute pulmonary embolism (PE) is a potentially lifethreatening disease, spanning a wide spectrum of clinical outcomes.1 Hemodynamically stable patients with preserved right ventricular (RV) size and function are classified as lowrisk patients and have an excellent short-term prognosis once therapeutic levels of anticoagulation therapy are established. 2In contrast, hemodynamically unstable patients are at high risk of death from worsening RV failure and cardiogenic shock, with a hospital mortality rate >15%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
670
3
29

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 877 publications
(754 citation statements)
references
References 24 publications
24
670
3
29
Order By: Relevance
“…The main principle is accessing the clot with a catheter and using high-frequency, low-power ultrasound to separate fibrin strands in order to enhance the penetration of thrombolytics [10]. In contrast to conventional systemic thrombolytics, USAT with low dose tPA infusion has the same bleeding risk as heparin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The main principle is accessing the clot with a catheter and using high-frequency, low-power ultrasound to separate fibrin strands in order to enhance the penetration of thrombolytics [10]. In contrast to conventional systemic thrombolytics, USAT with low dose tPA infusion has the same bleeding risk as heparin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…After assessing the risks and benefits of the available options for both the mother and fetus, the team reached a consensus to proceed with CDT using an ultrasound-enhanced EKOS catheter ( Figure 2). The goal was to minimize risks to the mother and fetus and simultaneously optimize RV recovery (7,8).…”
Section: Casementioning
confidence: 99%
“…These patients have right ventricular strain diagnosed either with echocardiogram, EKG, high Troponin and high BNP. Authors have suggested treating these patients via catheter driven techniques with or without thrombolytic therapy [5,6]. Our patients with submassive PE who were clinically stable but with evidence of RV strain were treated with IV heparin therapy for 5 -7 days then switched to Lovenox subcutaneously for 2 -4 weeks keeping the antifactor Xa in the range 0.5 IU/ml to 1.2 IU/ml.…”
Section: Editorialmentioning
confidence: 99%